PENCEGAHAN PENYALAHGUNAAN NARKOBA BAGI SISWA/I SMK FARMASI DI KABUPATEN SUMBAWA - Haedar Putra; Evi Gustia Kesuma; Raudatul Umroh; Julia Mujahadah Pratiwi (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2022)
The world of education must be managed as well as possible in order to be able to produce quality human resources. But along with the progress of the times, the rampant circulation and abuse of drugs has affected the mental and education of today's students. It is feared that students will fall into drug circles, either voluntarily because of their curiosity, or as a result of pressure from outsiders that can arise due to promiscuity. This service activity aims to provide information to students related to drug prevention. The method used is lecture and discussion. The sample in this study were 80 students of SMKI Pharmacy Sumbawa consisting of students in class X-XII. The activity was carried out on July 28, 2022 for 1 hour 20 minutes. The series of events in this activity are opening, core material, discussion, and closing. The result of this activity is that students are active in receiving information related to drug prevention efforts provided by the speaker. So it is hoped that the school can provide lessons or material about drugs in existing subjects.